Haemodialysis Alters the Index of Cardiac-Electrophysiological Balance - Abdul Rehman Arshad; Tayyaba Khan; Fuad Ahmad Siddiqi; Shabana Tahir; Shahid Ahmad; Mohsin Qayyum (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study electrocardiographic changes during haemodialysis and determine the relationship between electrolyte alterations and acid-base balance. Study Design: Cross-sectional analytical study.